Early and Prolonged Response to Pazopanib in a Patient with Multiple Metastases from Renal Cell Carcinoma: A Case Report. Issue 3 (May 2014) - Biasco, Elisa; Antonuzzo, Andrea; Cianci, Claudia; Derosa, Lisa; Marconcini, Riccardo; Farnesi, Azzurra; Galli, Luca
Aims and Background: In recent years, targeted agents have replaced cytokine therapy as the standard of care for patients with metastatic renal cell carcinoma. Methods and Study Design: We report a patient with multiple metastases from renal cell carcinoma treated with cytoreductive surgery and pazopanib. Results and Conclusions: The treatment resulted in an early and prolonged response, without toxicity.